2020
DOI: 10.1111/dmcn.14651
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spoken language comprehension in children with cerebral palsy: a systematic review

Abstract: To identify factors that are relevant for spoken language comprehension in children with cerebral palsy (CP), following the International Classification of Functioning, Disability and Health-Children and Youth (ICF-CY) framework. METHOD A systematic literature search was conducted using the electronic literature databases PubMed, Embase, PsycInfo, and Cochrane Library, from January 1967 to December 2019. Included studies involved children with CP, results regarding spoken language comprehension, and analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…Correlation analysis between the FCCS and epilepsy was not performed; however, the two children with a history of epilepsy, one current and one resolved, were classified by the SLP and parents in FCCS level V. A recent systematic review reported good-to-excellent quality evidence suggesting that other factors, such as brain lesions, motor severity, or motor type, in comparison to epilepsy, have a more direct effect on communication development in children with CP. 31 There was a stronger relationship between FCCS ratings and visual impairment for younger children with CP in this study (r s =0.70, p<0.001) compared to the fair correlation for older children with CP. 18 Pennington et al 32 found that visual function at 2 years predicts FCCS levels for children at 5 years of age.…”
Section: Relationship Between Fccs and Pemgcontrasting
confidence: 54%
See 1 more Smart Citation
“…Correlation analysis between the FCCS and epilepsy was not performed; however, the two children with a history of epilepsy, one current and one resolved, were classified by the SLP and parents in FCCS level V. A recent systematic review reported good-to-excellent quality evidence suggesting that other factors, such as brain lesions, motor severity, or motor type, in comparison to epilepsy, have a more direct effect on communication development in children with CP. 31 There was a stronger relationship between FCCS ratings and visual impairment for younger children with CP in this study (r s =0.70, p<0.001) compared to the fair correlation for older children with CP. 18 Pennington et al 32 found that visual function at 2 years predicts FCCS levels for children at 5 years of age.…”
Section: Relationship Between Fccs and Pemgcontrasting
confidence: 54%
“…It is important to note for this study that the presence or absence of an intellectual impairment was derived from parental report and/or file notes, which may have resulted in an over‐ or underestimation of intellectual impairment. Correlation analysis between the FCCS and epilepsy was not performed; however, the two children with a history of epilepsy, one current and one resolved, were classified by the SLP and parents in FCCS level V. A recent systematic review reported good‐to‐excellent quality evidence suggesting that other factors, such as brain lesions, motor severity, or motor type, in comparison to epilepsy, have a more direct effect on communication development in children with CP 31 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, birth history variables, including delivery mode, gestational age, birth weight, head circumference, body length, and Apgar score, will also be documented. Furthermore, a systematic review (Vaillant et al, 2020) indicated that the factors in some domains of the International Classification of Functioning, Disability and Health -Children and Youth framework are relevant for language comprehension in children with CP. According to this concept, children's motor type, motor distribution, hand function (MACS), gross motor function (GMFCS), hearing function, visual function, speech function, socioeconomic status, parental educational level, parental occupation, and birth order will be recorded.…”
Section: Demographic Datamentioning
confidence: 99%
“…Communication (receptive and/or expressive language) impairments are common comorbidities in patients with CP, with a prevalence ranging from 46 to 78% (Coleman et al, 2015(Coleman et al, , 2016Mei et al, 2016;Kristoffersson et al, 2020). Communication problems result in poor prospects of engagement and social participation in children with CP across a range of activities, including self-development, social functioning, and learning (Pennington et al, 2019;Vaillant et al, 2020). Particularly by the time these children enter school, communication skills greatly impact school readiness, which affects later social and academic success as well as economic and health outcomes (High, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It follows that children with ND are also frequently affected by speech disorders, which encompass a range of distinct disorders, such as articulation and phonological disorders, dysarthria, and childhood apraxia of speech (Dodd & Morgan, 2017). Children with ND may suffer from intellectual disability (ID) as well (Bottcher, 2010;Koziol et al, 2014), as a consequence of a shared cause, and language comprehension problems are often found in children with ND and ID (Vaillant et al, 2020), even if the co-existence of NDs, IDs, and language disorders does not always share a known etiology (d 'Souza et al, 2017). It is still unclear whether this delayed language development can be explained by cognitive disturbance, or whether it is a result of a lack of interaction and experience of the outside world (Shriberg et al, 2019;Srour & Shevell, 2014).…”
mentioning
confidence: 99%